Support and follow-up needs of patients discharged from intensive care after severe COVID-19: a mixed-methods study of the views of UK general practitioners and intensive care staff during the pandemic’s first wave - CASTRO AVILA, ANA CRISTINA; Laura Jefferson; Veronica Dale; Karen Bloor (My University, 2021)
ObjectivesTo identify follow-up services planned for patients with COVID-19 discharged from intensive care unit (ICU) and to explore the views of ICU staff and general practitioners (GPs) regarding these patients’ future needs and care coordination.DesignThis is a sequential mixed-methods study using online surveys and semistructured interviews. Interview data were inductively coded and thematically analysed. Survey data were descriptively analysed.SettingGP surgeries and acute National Health Service Trusts in the UK.ParticipantsGPs and clinicians leading care for patients discharged from ICU.Primary and secondary outcomesUsual follow-up practice after ICU discharge, changes in follow-up during the pandemic, and GP awareness of follow-up and support needs of patients discharged from ICU.ResultsWe obtained 170 survey responses and conducted 23 interviews. Over 60% of GPs were unaware of the follow-up services generally provided by their local hospitals and whether or not these were functioning during the pandemic. Eighty per cent of ICUs reported some form of follow-up services, with 25% of these suspending provision during the peak of the pandemic and over half modifying their provision (usually to provide the service remotely). Common themes relating to barriers to provision of follow-up were funding complexities, remit and expertise, and communication between ICU and community services. Discharge documentation was described as poor and lacking key information. Both groups mentioned difficulties accessing services in the community and lack of clarity about who was responsible for referrals and follow-up.ConclusionsThe pandemic has highlighted long-standing issues of continuity of care and complex funding streams for post-ICU follow-up care. The large cohort of ICU patients admitted due to COVID-19 highlights the need for improved follow-up services and communication between specialists and GPs, not only for patients with COVID-19, but for all those discharged from ICU.
Keywords: covid-19; intensive & critical care; rehabilitation medicine; covid-19; critical care; follow-up studies; general practitioners; humans; pandemics; patient discharge; sars-cov-2; state medicine; united kingdom; article; awareness; cohort analysis; controlled study; coronavirus disease 2019; descriptive research; female; follow up; general practitioner; health care need; hospital discharge; human; intensive care; intensive care unit; male; medical documentation; national health service; pandemic; procedures; semi structured interview; thematic analysis; united kingdom; follow up; intensive care; pandemic; united kingdom